Cardiorespiratory fitness is impaired and predicts mid‐term postoperative survival in patients with abdominal aortic aneurysm disease. Issue 11 (13th October 2018) - Rose, G. A.; Davies, R. G.; Appadurai, I. R.; Lewis, W. G.; Cho, J. S.; Lewis, M. H.; Williams, I. M.; Bailey, D. M.
Abstract : New Findings: What is the central question of this study? To what extent cardiorespiratory fitness is impaired in patients with abdominal aortic aneurysmal (AAA) disease and corresponding implications for postoperative survival requires further investigation. What is the main finding and its importance? Cardiorespiratory fitness is impaired in patients with AAA disease. Patients with peak oxygen uptake of <13.1 ml O2  kg −1  min −1 and ventilatory equivalent for carbon dioxide at anaerobic threshold ≥34 are associated with increased risk of postoperative mortality at 2 years. These findings demonstrate that cardiorespiratory fitness can predict mid‐term postoperative survival in AAA patients, which may help to direct care provision. Abstract: Preoperative cardiopulmonary exercise testing is a standard assessment of cardiorespiratory fitness (CRF) and risk stratification. However, to what extent CRF is impaired in patients undergoing surgical repair of abdominal aortic aneurysm (AAA) disease and the corresponding implications for postoperative outcome requires further investigation. We measured CRF during an incremental exercise test to exhaustion using online respiratory gas analysis in patients with AAA disease ( n  = 124, aged 72 ± 7 years) and healthy sedentary control subjects ( n  = 104, aged 70 ± 7 years). Postoperative survival was examined for association with CRF, and threshold values were calculated for independent predictors of mortality. Patients who underwent preoperative cardiopulmonary exercise testing before surgical repair had lower CRF [age‐adjusted mean difference of 12.5 ml O2  kg −1  min −1 for peak oxygen uptake ( V ̇ O 2 peak ), P  < 0.001  versus control subjects]. After multivariable analysis, both V ̇ O 2 peak and the ventilatory equivalent for carbon dioxide at anaerobic threshold ( V ̇ E / V ̇ C O 2 − AT ) were independent predictors of mid‐term postoperative survival (2 years). Hazard ratios of 5.27 (95% confidence interval 1.62–17.14, P  = 0.006) and 3.26 (95% confidence interval 1.00–10.59, P  = 0.049) were observed for V ̇ O 2 peak  < 13.1 ml O2  kg −1  min −1 and V ̇ E / V ̇ C O 2 − AT ≥ 34, respectively. Thus, CRF is lower in patients with AAA, and those with a V ̇ O 2 peak  < 13.1 ml O2  kg −1  min −1 and V ̇ E / V ̇ C O 2 − AT ≥ 34 are associated with a markedly increased risk of postoperative mortality. Collectively, our findings demonstrate that CRF can predict mid‐term postoperative survival in AAA patients, which may help to direct care provision. Abstract :